IMPLEMENTASI KERJASAMA INDONESIA DAN BRAZIL DI BIDANG KEAMANAN DAN INDUSTRI PERTAHANAN TAHUN 2010-2017 - Niken Rahmadhiana Putri, (2022)
This study will examine the implementation of cooperation between Indonesia and Brazil in the defense industry in 2010-2017. This collaboration began with the signing of an MoU in 2010 which included the purchase of the Super Tucano EMB-314, MLRS Astros II Technology Transfer, deployment of defense attaches and joint military exercises. This study uses a qualitative method approach by looking for data that is in accordance with the research topic, the results show that it is in Indonesia's interest to cooperate in the defense industry with Brazil because currently Indonesia wants its independence in producing defense equipment and modernizing defense equipment. the development of an increasingly real threat so that to protect the territory of the Republic of Indonesia, modern defense equipment is needed. And the benefits for Indonesia, such as the better Indonesian defense equipment, soldier education, sophisticated military equipment, and the placement of defense attaches at the Indonesian Embassy in Jakarta. Keywords: Defence industry, Indonesia, Brazil, Military defense cooperation, Transfer of Technology